New record of the gaper Champsodon nudivittis (Ogilby, 1895) from the deep waters of north-east Arabian Sea with notes on its biology - Ganga, U.; Jinesh, P. T.; Beni, N. (Indian Journal of Fisheries, 2014)
The gaper Champsodon nudivittis is reported as the first record of the species in the northern Arabian Sea where it was caught at 280 -390 m depths between 19 and 210 N latitudes. Study confirmed the presence of a sizeable self-regenerating population of C. nudivittis in the northern Arabian Sea comprising of reproductively active, mature fish, which was believed to be absent so far. The size range of the specimens caught was 55-105 mm with modal size 75-85 mm. Females were significantly dominant (p<0.05) in > 60 mm size groups, with a sex ratio of 1:4.3. Catch was dominated by mature females, with an estimated Lm of 74 mm. Mean absolute fecundity was 740Â±156 eggs and mean relative fecundity 205Â±97 eggs per gram body weight. It is a carnivorous predator, feeding on young of several commercially important fishery resources such as the pandalid shrimps, sergestid shrimps (Acetes) and the Indian codlet Bregmaceros spp. found in the northern Arabian Sea.